Condicionamento fisiológico em sementes de jucá (Libidibia ferrea (Mart. ex Tul.) L.P. Queiroz var. ferrea) submetidas a salinidade - Oliveira, Valéria Nayara Silva de (2020)
The jucá ((Mart. ex Tul.) L.P. Queiroz var. ferrea) belongs to the Fabaceae family, with a distribution in the North and Northeast regions, commonly used in household treatment, civil construction, and the degraded areas recovery. Although it is a species to the semiarid, may have compromised germination and vigor due to the water or soil salinity, conditions prevalent in Northeast Brazil. In this context, the objective was to evaluate the germination and vigor of L. ferrea seeds submitted to salt stress and the effects of priming on the tolerance of seeds offered to salinity. For this, we carried two experiments, the first being carried out in a completely randomized experimental design, in a 2 x 6 factorial scheme, with two lots and six levels of salinity (4, 8, 12, 16, and 20 dS m-1) and distilled water, with four repetitions of 25 seeds. We put the seeds to germinate on a paper towel substrate previously moistened with NaCl solutions and placed them to grow in a germination chamber at 25 °C for 20 days. In the second experiment, the conditioning consisted of placing the seeds on a paper towel-type substrate moistened with polyethylene glycol solutions (PEG 6000) at the osmotic potentials of -0.2 and -0.4 MPa for 60 and 84 hours, respectively, and with distilled water for 36 hours at 25 °C. Then, we place conditioned and unconditioned seeds to germinate on a paper towel substrate moistened with NaCl solutions (12, 16, and 20 dS m-1) and distilled water (0 dS m-1) at 25 ºC. In both experiments, the variables analyzed were: first count, germination, seedling length (shoot and root), and dry matter (shoot and root). The response to salinity varied between L. ferrea lots, and germination was negatively affected by the increase in salinity in only one lot. At the same time, vigor was impaired from 12 dS m-1 in the two lots taken. The seeds' hydro-priming and osmo-priming provided greater tolerance to salt stress than no priming seeds, up to 16 dS m-1